Establishing a publicly available national database of US news articles reporting agriculture‐related injuries and fatalities. Issue 8 (22nd May 2018) - Weichelt, Bryan; Salzwedel, Marsha; Heiberger, Scott; Lee, Barbara C.
Abstract : Background: The AgInjuryNews system and dataset are a news report repository and information source for agricultural safety professionals, policymakers, journalists, and law enforcement officials. Methods: AgInjuryNews was designed as a primary storage and retrieval system that allows users to: identify agricultural injury/fatality events; identify injury agents and emerging issues; provide safety messages for media in anticipation of trends; and raise awareness and knowledge of agricultural injuries and prevention strategies. Data are primarily collected through Google Alerts and a digital media subscription service. Articles are screened, reviewed, coded, and entered into the system. Results: As of January 1, 2018, the system contained 3028 unique incidents. Of those, 650 involved youth, and 1807 were fatalities. The system also had registered 329 users from 39 countries. Conclusions: AgInjuryNews combines injury reports into one dataset and may be the most current and comprehensive publicly available collection of news reports on agricultural injuries and deaths.